Flood Early Warning System Using Ultrasonic and Rainfall Sensors IoT-Assisted with Smartphone Display - Ramadhiani, Dhea Dinda; Yulkifli, Yulkifli (Journal of Experimental and Applied Physics, 2023)
The increasing incidence of floods in Indonesia every year is in line with the losses they incur, thus requiring preventive measures such as an early warning system that is more effective than conventional systems. This early warning system uses Internet of Thing (IoT) technology which utilizes the internet so that information on potential floods can be accessed in real time on a smartphone and provides an alarm according to the potential for flooding obtained from two flood indicator data, namely rainfall and water level. This study uses NodeMCU ESP8266 as a microcontroller to read and process data from the ultrasonic HC-SR04 to detect water levels and tipping buckets to detect rainfall. The IoT system that is connected to the internet then reads and sends data that is processed by the microcontroller to be displayed on a smartphone via the Blynk application. Sensor testing was carried out by varying 10 data to obtain an average relative accuracy of 99.28% on ultrasonic and an average relative accuracy of 98.75% on tipping buckets. Overall, the system works well and provides accurate information if it is connected to the internet.